2020
DOI: 10.1021/acs.est.0c02982
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Nonalignment of Methods and Approaches Used in Microplastic Research to Consistently Characterize Risk

Abstract: The lack of standard approaches in microplastic research limits progress in the abatement of plastic pollution. Here, we propose and test rescaling methods that are able to improve the alignment of methods used in microplastic research. We describe a method to correct for the differences in size ranges as used by studies reporting microplastic concentrations and demonstrate how this reduces the variation in aqueous-phase concentrations caused by method differences. We provide a method to interchange between nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
251
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(265 citation statements)
references
References 39 publications
7
251
1
3
Order By: Relevance
“…36 This mechanism would imply that the mass-based TTF GUT values would be similar regardless of actual particle size, as long as particles would be ingestible. 36,52 The current finding that NP and MP with large size differences yield very similar TTF GUT under the same exposure conditions supports this hypothesis. We emphasize that this value only applies to the 28 d time point.…”
Section: Comparison Of Accumulation Kinetics and Trophic Transfer Factors Between Np And Mpsupporting
confidence: 75%
“…36 This mechanism would imply that the mass-based TTF GUT values would be similar regardless of actual particle size, as long as particles would be ingestible. 36,52 The current finding that NP and MP with large size differences yield very similar TTF GUT under the same exposure conditions supports this hypothesis. We emphasize that this value only applies to the 28 d time point.…”
Section: Comparison Of Accumulation Kinetics and Trophic Transfer Factors Between Np And Mpsupporting
confidence: 75%
“…Rescaling the MP concentrations to the full MP size continuum was thus necessary to not underestimate the concentrations. 12 Furthermore, in doing so, we accounted for the smallest particles that are more relevant for accumulation in the body and potential toxicity. 9 , 13 The estimated power-law exponent for food in the present study is in excellent agreement with the exponents reported previously for PSDs of MPs in marine and freshwater environments.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed approach for extracting this information is explained in the Supporting Information. We fitted the PSDs for 29 datasets from our literature review with the power-law function ( Figure S1 and Table S4 ), according to Koelmans et al 12 (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last year, the two teamed up with colleagues to use this model in computer simulations that predict how often fish would encounter microplastics small enough to eat, and the likelihood of eating enough specks to affect growth. The researchers found that at current microplastic pollution levels, fish run that risk at 1.5% of locations checked for microplastics 6 . But there are likely to be hotspots where the risks would be higher, says Koelmans.…”
Section: Microplastics To Scalementioning
confidence: 99%